Factors Predicating Loss to Follow-Up With Rescreening in Early Hearing Detection and Intervention Programs. Issue 2 (April 2019) - Zeitlin, Wendy; Auerbach, Charles; Mason, Susan; Spivak, Lynn; Erdman, Andrew
Most infants born in the United States are screened for hearing loss prior to hospital discharge in Early Hearing Detection and Intervention (EHDI) programs; however, many infants who do not pass their screening do not return for recommended rescreening and are considered lost to follow-up (LTF). This research addresses this by examining factors related to LTF at the point of rescreening. A prospective longitudinal study tracked 166 families whose newborns were referred for additional testing upon hospital discharge. Analysis identified two factors related to being LTF: parents' perceptions of hearing loss as having the potential to impact their child's future and maternal depression; however, social support moderated the impact of maternal depression. Specific implications for working with families is discussed.